COMPARATIVE ANALYSIS OF RECONSTRUCTIVE METHODS FOR CONGENITAL DEFECTS AND DEFORMITIES OF THE FACIAL BONES - Akbar Mamanazarova (Western European Studies, 2025)
Fixing problems with the bones in the face that happened because of an injury is really hard to do. The doctor has to make sure the face works properly and also looks okay. There are ways that doctors can fix these problems. They can take bone from one part of the body. Put it in the face. They can also use a technique that helps the bone grow back on its own. Another way is to take tissue from one part of the body and attach it to the face using blood vessels. Doctors can even make implants that are just for the patient. Using bone from the patients body is good because it will not cause any problems and it will last a long time but it only works for small or medium sized problems. If the problem is really bad doctors can use a technique that helps the bone and the soft tissue, around it grow back at the same time. Restoration of acquired bone defects and deformities is what doctors are trying to do when they use these techniques. Free tissue transfer is versatile for large, composite defects, offering reliable functional and aesthetic restoration, while PSIs deliver precise anatomical reconstruction and reduced operative time for complex defects. Comparative analysis indicates that the choice of method should be individualized, considering defect characteristics, patient factors, and available resources. Multimodal strategies often optimize outcomes, and advances in imaging, virtual planning, and biomaterials continue to enhance the precision and predictability of facial reconstruction
Keywords: Facial bone defects; Bone grafting Distraction osteogenesis; Distraction osteogenesis